PMO-054 Laparoscopic silastic ring loop gastric bypass (SR-LGBP): a single centre experience. (28th May 2012) - Clarke, M; Pearless, L; Booth, M
Abstract : Introduction: Laparoscopic loop gastric bypass (LGBP) may represent a simpler alternative procedure to Roux-en-Y gastric bypass. Placement of a silastic ring (SR) may minimise weight regain. This study reports upto 5-year outcomes following laparoscopic SR-LGBP. Methods: Retrospective analysis of consecutive patients undergoing SR-LGBP between August 2005 and January 2008. A 15–20 ml lesser-curve gastric pouch was created with 32Fr orogastric bougie, handsewn gastroenterostomy 150–200 cm distal to the ligament of Treitz and a 6.5–7 cm silastic ring around the gastric pouch. Results: 156 patients (78% female, 22% male) with a mean (range) age of 44 (18–63) years, pre-op weight of 129 (83–197) kg and BMI of 46 (35–64) kg/m 2 underwent surgery. 87% had pre-operative comorbidities and median (range) follow-up was 35 (6–72) months. Mean (SD) % excess weight loss (EWL) at 6, 12, 24, 36 and 60 months was 74.6 (19.5), 93.4 (21.1), 98.8 (27.6), 93.5 (20.1) and 89 (16.1) respectively. 37% had complete resolution of comorbidities and 67.3% required vitamin/mineral supplementation. Overall 90 (57.7%) patients; 12 (7.7%) early and 78 (50%) late, reported minor complications, the commonest being reflux (10%) or vomiting/dysphagia/food intolerance (16%). 39 (25%) patients; 4 (2.6%) early and 35 (22.4%) late, reported major complications requiring hospitalisation. Marginal ulcer and anastomotic stenosis were seen in 7.7% and 9.6% respectively. 16 (10.3%) patients required reoperation: 6 (3.8%) bile reflux, 3 (1.9%) ring removal, 2 (1.3%) perforation and 5 (3.2%) other. There were no deaths. Conclusion: SR-LGBP achieves excellent EWL with low mortality. While vomiting, food intolerance, reflux, stricture and stomal ulceration were relatively common, only 10% required reoperation. Competing interests: None declared.